A Promising Recombinant Herpesvirus of Turkeys Vaccine Expressing PmpD-N of Chlamydia psittaci Based on Elongation Factor-1 Alpha Promoter - Liu, Shanshan; Sun, Wei; Huang, Xuefei; Zhang, Wen; Jia, Changqing; Luo, Jie; Shen, Yihua; El-Ashram, Saeed; He, Cheng (Frontiers in Veterinary Science, 2017)
The obligate intracellular Gram-negative bacterium Chlamydia psittaci (C. psittaci) often causes avian chlamydiosis and influenza-like symptoms in humans. However, the commercial subunit C. psittaci vaccine could only provide a partial protection against avian chlamydiosis due to poor cellular immune response. In our previous study, a recombinant herpesvirus of turkeys (HVT)-delivered vaccine against C. psittaci and Marek’s disease based on human cytomegalovirus (CMV) promoter (rHVT-CMV-pmpD) was developed and provided an effective protection against C. psittaci disease with less lesions and reduced chlamydial loads. In this study, we developed another recombinant HVT vaccine expressing the N-terminal fragment of PmpD (PmpD-N) based on human elongation factor-1 alpha (EF-1α) promoter (rHVT-EF-pmpD) by modifying the HVT genome within a bacterial artificial chromosome (BAC). The related characterization of rHVT-EF-pmpD was evaluated in vitro in comparison with that of rHVT-CMV-pmpD. The expression of PmpD-N was determined by western blot. Under immunofluorescence microscopy, PmpD-N protein of both two recombinant viruses was located in the cytoplasm and on the cell surface. Growth kinetics of rHVT-EF-pmpD was comparable to that of rHVT-CMV-pmpD, and the growth rate of rHVT-EF-pmpD was apparently higher than that of rHVT-CMV-pmpD on 48, 72 and 120 h post infection. Macrophages activated by rHVT-EF-pmpD could produce more nitric oxide and IL-6 than that activated by rHVT-CMV-pmpD. In this study, a recombinant HVT vaccine expressing PmpD-N based on EF-1α promoter was constructed successfully, and a further research in vivo was needed to analyze the vaccine efficacy.